A periodic problem for the inhomogeneous equation of string oscillations - Mitropolskiy, Yu. A.; Khoma, G. P.; Tsynalko, P. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study a periodic problem for the equation u tt−uxx=g(x, t), u(x, t+T)=u(x, t), u(x+ω, t)= =u(x, t), ℝ2 and establish conditions of the existence and uniqueness of the classical solution.